Faktor-Faktor yang Berhubungan dengan Kejadian ISPA pada Balita - Dita Rahmadanti; Rony Darmawansyah Alnur (Politeknik Baubau, 2023)
Background: Acute Respiratory Tract Infection (ARI) is a health problem that commonly affects children under five. Aspects that are susceptible to the incidence of ARI include education, knowledge, humidity and smoking habits. Objective: To determine the factors associated with the incidence of ARI in children under five years of age in the Working Area of UPTD Puskesmas Babelan 1 Bekasi Regency in 2023. Sample: The sample in this study were 40 cases and 40 controls. Methods: This study used a case control design with total sampling technique for the case group and purposive sampling technique for the control group. Results: The results of the chi-square test analysis showed maternal education (pvalue = 0.002), maternal knowledge (pvalue = 0.035), room air humidity (pvalue = 0.013) and smoking habits of family members (pvalue = 0.036). Conclusion: There is a relationship between maternal education (pvalue = 0.002), maternal knowledge (pvalue = 0.035), room air humidity (pvalue = 0.013) and smoking habits of family members (pvalue = 0.036) with the incidence of ARI in toddlers in the Working Area of UPTD Puskesmas Babelan 1 Bekasi Regency in 2023.